2020
DOI: 10.3389/fpls.2020.569905
|View full text |Cite
|
Sign up to set email alerts
|

The Global Durum Wheat Panel (GDP): An International Platform to Identify and Exchange Beneficial Alleles

Abstract: Representative, broad and diverse collections are a primary resource to dissect genetic diversity and meet pre-breeding and breeding goals through the identification of beneficial alleles for target traits. From 2,500 tetraploid wheat accessions obtained through an international collaborative effort, a Global Durum wheat Panel (GDP) of 1,011 genotypes was assembled that captured 94–97% of the original diversity. The GDP consists of a wide representation of Triticum turgidum ssp. durum modern germplasm and land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 110 publications
8
56
1
Order By: Relevance
“…The large differences between the agronomic performance of durum wheat landraces and modern cultivars identified in the current study agree with the contrasting genetic background of both germplasm types reported in previous studies (Soriano et al, 2016 ; Mazzucotelli et al, 2020 ). Group mean analysis, observation of frequency distributions for each group and the multivariate analysis (PCA for traits) indicated that the significant yield advantage of modern cultivars was associated with greater number of grains per spike and a drastically improved harvest index but not with any difference in kernel weight, confirming results from previous studies (Gale and Youssefian, 1985 ; De Vita et al, 2007 ; Royo et al, 2007 , 2008 ; Fayaz et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…The large differences between the agronomic performance of durum wheat landraces and modern cultivars identified in the current study agree with the contrasting genetic background of both germplasm types reported in previous studies (Soriano et al, 2016 ; Mazzucotelli et al, 2020 ). Group mean analysis, observation of frequency distributions for each group and the multivariate analysis (PCA for traits) indicated that the significant yield advantage of modern cultivars was associated with greater number of grains per spike and a drastically improved harvest index but not with any difference in kernel weight, confirming results from previous studies (Gale and Youssefian, 1985 ; De Vita et al, 2007 ; Royo et al, 2007 , 2008 ; Fayaz et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the Expert Working Group on Durum Wheat Genomics and Breeding, in the frame of the Wheat Initiative, and the International Durum Wheat Genome Sequencing Consortium developed two large germplasm collections: The Global Durum Wheat Panel (GDP) and the Tetraploid wheat Germplasm Collection (TGC), respectively [ 34 , 35 ]. Both collections are suitable for identifying beneficial alleles for traits of agronomic importance to be used in breeding and pre-breeding programs.…”
Section: Conservation ‘In Situ’ and ‘Ex Situ’ Of The Main Cereal Collections And Availability Of Databasesmentioning
confidence: 99%
“…If focusing on specific geographic areas has the advantage of exploring within a range of genotypes well adapted to that environment, examining wider collections opens the possibility of investigating the genetic relationship across landraces spread around the world, and having a more precise estimation of the genetic diversity within the group of landraces and with respect to advanced breeding lines or modern cultivars. To quote some examples, studies carried out on panels of hundreds of landraces have been considered in durum and common wheat [ 35 , 59 , 60 ], barley [ 61 , 62 ] and rye [ 63 ]. In general, a higher genetic diversity has been observed in the group of landraces compared to the groups of advanced breeding lines and modern cultivars, indicating landraces as a useful source of variation for breeding.…”
Section: Exploration Of Genetic Diversity and Population Structurementioning
confidence: 99%
See 2 more Smart Citations